Roaming the Virtual Lanes: Motorcyclists' Lane Filtering- Splitting Manoeuvres and Exposure to Road Crashes - Ibrahim, M.K.A.; Mohamed Jamil, H.; Abdul Manan, M.M.; Hanowski, R.J. (Journal of the Society of Automotive Engineers Malaysia, 2021)
There is an urgent need to address motorcycle safety issues, especially in countries with high motorcycle ridership. This paper provides an overview of the research related to motorcycle movements in mixed traffic and their associated crash risk. It also highlights the factors that influence the risk of a crash from the perspective of motorcyclists and other motorists. The potential countermeasures to address the risk factors were also explored and suggestions were presented to improve the current status quo.